Real options: A review of select theories and applications - Renato E. Reside (University of the Philippines, School of Economics (UPSE), 2022)
This paper is an introduction to the concepts and methods used in the field of real options as they relate to investments. The analog between financial and real options is explained. The discrete version of a model is introduced, then solutions to the canonical model in continuous time using dynamic programming and contingent claims analysis are discussed. Finally, the paper covers extensions of the canonical model to various other option structures.
Keywords: E2; E22; G11; G31; 330; Real options analysis; Investment theory